BIODIESEL PRODUCTION FROM PALM OIL OVER SYNTHESIZED CERIA NANOMATERIAL - OLUWASEGUN, OYENUBI ABA YOMI (2017)
Many high yielding catalyst rangmg from homogenous, heterogeneous and biocatalysts have been used for biodiesel production. However, high amount of energy is still required to mix the reactants (oils and alcohols) during reactions. Therefore, this study examine four ceria nanomaterials that are capable of increasing miscibility by lowering the surface tension at the interface of the reactants. The synthesized ceria nanomaterials namely; titanium doped ceria, cerium dodecyl trimethyl ammonium bromide, cerium hexadecyl trimethyl ammonium bromide and cerium hexadecyl trimethyl ammonium chloride were characterized by x-ray diffraction techniques (XRD), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy and surface area and pore size analyzer. After which they were used for transesterificationof palm oil. A 0.4 wt. % Ce02-Ti02 gave a yield of 70.6 % at 55 OC, 12:1 methanol oil ratio, and 1.0 wt. % catalyst loading in 150 minutes. The density and viscosity ofbiodiesel produced are 920.9 kg/m3 and 12 N.s/m2 respectively.